Lethality level casualty assessment method for earthquake landslide hazards based on the expansion effect of the mortality rate - Xia Chaoxu; Qi Wenhua; Li Huayue; Nie Gaozhong (Scientific Reports)
Abstract Rapid assessment of earthquake disaster losses is crucial for effective emergency rescue operations, with post-earthquake geological hazards constituting a significant component. In this study, we conducted extensive field investigations of historical earthquakes in China, collecting mortality data categorized by cause of death. Through analysis of historical earthquake records, we determined the proportions of fatalities attributed to different causes, integrating seismic intensity data, population distribution information, to establish intensity-dependent mortality rates for earthquake-triggered landslides. We systematically compiled the spatial distribution patterns, occurrence frequency, and density characteristics of landslides induced by historical earthquakes through field surveys and literature analysis. By comparing these results with historical intensity-mortality relationships, we quantified the amplifying effect of secondary geological hazards on mortality rates. The results demonstrate that landslide hazards exhibit significant mortality amplification at intensities of VIII and above, with this amplification effect intensifying progressively with higher seismic intensities. Using these findings, we developed a lethality matrix for earthquake-triggered landslides by incorporating intensity-mortality relationships. Validation using historical earthquake cases shows that the calculated casualties error within ± 30% of actual recorded values across different regions and magnitudes. This study achieves two objectives (1) verifies the validity and regional applicability of the proposed matrix methodology for landslide casualty assessment, and (2) provides a scientific foundation for developing regionalized assessment matrices, thereby enhancing post-earthquake emergency response capabilities.